Selective fluoride ion sensing using novel quinoline chemosensor insights into kinetics and molecular logic gate functions - A. V. Ashwathi; Sabeel M. Basheer (Scientific Reports)
Abstract CQHC, a novel colorimetric fluorescent sensor, developed for the selective sensing of ions and well characterised, including SC-XRD. It demonstrated selective sensing for Co2+, Zn2+, Hg2+ and F– using absorbance titration at 420 nm, 446 nm and the binding constants estimated follows the order F– > Co2+ > Hg2+ > Zn2+. On light of this, molecular logic gate was built for CQHC’s selective multi-ion detection. However, fluorescence titration analysis revealed that CQHC is solely selective for F– ions. This conclusion was validated by 1H–NMR titration, clearly showed deprotonation occurs from N3–H. Fluorescent decay titration, kinetic investigations and computational studies all contributed to the selective sensing of F–. According to TD–DFT calculations, added fluoride ion interacts with N3–H proton and deprotonates to generate F–H in the excited state.